Effect of Carbonation on Physicochemical Characteristics of Tomato Based Beverage - Ashish Dixit; Manoj Kumar Jaipal; Ramesh V.; Manju G. (Archives of Current Research International, 2025)
Tomato based carbonated beverage was developed using optimization techniques of response surface methodology. Effect of carbonation on tomato-based beverage was also investigated. Three independent variables were taken into account: tomato juice (A; 10–30%), sugar solution (B; 12–18 0B), and carbonation concentration (C; 90–110 psi) for the optimization of tomato based carbonated beverage. Twenty experimental runs were carried out to determine the impact of independent variables, such as pH, acidity, vitamin C, and overall acceptability, on product responses. The ideal conditions were determined to be 30% tomato juice, 18 0B sugar solution, and 100 psi carbonation concentration. Changes in physicochemical properties of tomato based carbonated beverage during storage were also investigated. pH and vitamin-C content of the tomato based carbonated beverage sample were gradually decreased from 4.50 to 4.10 and 17.91 mg/100 g to 12.40 mg/100 g, respectively whereas titratable acidity gradually increased from 0.28 % to 0.39% during storage period.